TEACHERSâ€™ SPIRITUALITY AND CLASSROOM MANAGEMENT AMONG PAROCHIAL SCHOOLS IN THE ARCHDIOCESE OF JARO - Perales, Nancy Canten (IDEAS: Journal of Management & Technology, 2025)
The study aimed to determine the level of teachersâ€™ spirituality and extent of classroom management of one hundred and fifty-nine (159) teachers of the Parochial Schools in the Archdiocese of Jaro. Foreign and local literatures related to teachersâ€™ spirituality and classroom management were reviewed in relation to their relevance and implications to the study.Â  A validated and reliability tested researcher-made questionnaire was used to gather the needed data from randomly selected respondents.Â  Statistical tools used to analyze and interpret were frequency counts, percentage, weighted mean, Mann-Whitney U-test and Spearman rank.Â  The findings of the study revealed that the level of teachersâ€™ spirituality was â€œhighâ€ and the extent of classroom management was â€œvery highâ€. There was no significant difference in the level of teachersâ€™ spirituality among the respondents when they were grouped according to selected profile. There was no significant difference in the extent of classroom management among the respondents when they were grouped according to selected profile. The finding has highly significant positive correlation between the level of teachersâ€™ spirituality and the extent of classroom management among respondents. Results suggest that teachersâ€™ spirituality and classroom management among the Parochial Schools in the Archdiocese of Jaro has manifested in a remarkable manner and provides a functional view of what direction the administration especially the school directors, principals, and teachers to the continuous development of the spiritual growth of the teachers and the sustenance of the classroom management practices. Â